2017
DOI: 10.1016/j.ajo.2017.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Late Solitary Extraocular Recurrence From Previously Resected Iris Melanoma

Abstract: Patients undergoing iris melanoma resection are at risk of developing late solitary extraocular relapse even more than 30 years after surgery. In the absence of an intraocular component, diagnosis may be challenging, as tumors mimic a primary conjunctival lesion. Management by excisional biopsy followed by adjuvant therapy was successful, and histopathology and genetic analysis supported a diagnosis of extraocular uveal tumor spread rather than a primary conjunctival tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Recurrence rate was 7.7% in their series [23]. Fabian et al reported four cases with extraocular relapse after previously resected iris melanoma at a mean of 21 years following initial surgery [24]. This report highlights the need for long-term follow-up for patients that previously underwent melanoma resection.…”
Section: Discussionmentioning
confidence: 78%
“…Recurrence rate was 7.7% in their series [23]. Fabian et al reported four cases with extraocular relapse after previously resected iris melanoma at a mean of 21 years following initial surgery [24]. This report highlights the need for long-term follow-up for patients that previously underwent melanoma resection.…”
Section: Discussionmentioning
confidence: 78%
“…The other 2 cases with a more UM-like profile (2 and 3) had no metastases at the point of study, but did have some characteristic indicators of poor prognosis, including those that may predispose to metastasis over a longer period. 7,13,20,25,31,32 Extended observation may clarify the association. For cases 4, 5, and 6, there was no consistent biomarker that related to the development of metastasis, and just as with conjunctival melanoma, further biomarkers would be advantageous.…”
Section: Discussionmentioning
confidence: 88%
“…Evidence suggests that iris melanomas also exhibit abnormalities in other chromosomes, which are less commonly affected in posterior uveal melanomas. These include changes in chromosome 9p, which is more frequently associated with cutaneous melanoma, as well as rearrangements involving chromosome 18 [ 57 ]. Studies have indicated that iris melanomas exhibit mutations shared with both posterior UMs and cutaneous melanomas (CM) [ 58 ].…”
Section: Genetic Basis Of Uveal Melanomamentioning
confidence: 99%